Strategi Pengembangan Ekonomi Kreatif berbasis One Village One Product (OVOP) Pada Kerajinan Rotan Putra Bali di Desa Seputih Kabupaten Jember - Hakim, Moch. Abdul Malik; Razek, Abdur; Nuraini, Sukaesih Intan; Amelia, Rika; Riska, Ifroh Naila; Hasanah, Alfi Nur; Khasanah, Siti Zaidatul; Santi, Indriana Laila; Fauziah, Nita Arini; Pratama, Hendi Yoga; Muzayyin, Muzayyin (Journal of Health, Education, Economics, Science, and Technology, 2025)
This study aims to examine the development strategy of Putra Bali rattan craft business in Seputih Village, Mayang District, Jember Regency, Using the One Village One Product (OVOP) approach. This business is a real representation of a creative economy based on local potential that has successfully penetrated the global market. The study used a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The results of the study showed that the strategies implemented included market expansion through digital marketing and showrooms in Bali, product development through material and design diversification, and innovation to maintain product originality. Despite facing challenges such as limited production capacity, prpduct quality, and minimal technological support from the government, this business was able to provide a significant ecomomic impacton the local community. The One Village One Product (OVOP) approach has proven effective in encouraging the strengthening of local identity and increasing product competitiveness in the international market.